Digital Political Communication on Twitter: Analysis of Gerindra Party’s Branding and Voter Engagement in Indonesia’s 2024 Election​ - Suparto, Diryo; Kushandayani; Dwimawanti, Ida Hayu; Yuniningsih, Tri; Habibullah, Akhmad; Bhandari, Rahul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
Social media confers numerous benefits that exert substantial influence within society, establishing Twitter as a prominent platform for political communication. This research examines the effect of Gerindra Party's Twitter account on shaping voter engagement in the 2024 election. The Gerindra Party maintains the Twitter account named 'Gerindra', which has published 3,250 tweets and has garnered 679,854 followers.  The research employs a descriptive qualitative method to analyze the Twitter accounts of the Gerindra and Prabowo parties, specifically the accounts of Gerindra and Prabowo.  In analyzing the data, the NVivo 14 Plus application is used to explore the various relationships and networks within the version.  The data analysis process in this research begins with the data input stage, which retrieves data from Twitter using the NCapture feature in NVivo. This stage encompasses data collected from the start of the active account, followed by coding, exploration, data visualization, data presentation, and conclusion.  The study reveals that the Gerindra Party utilizes Twitter strategically for political communication and digital branding, thereby shaping its public image and fostering voter loyalty. It finds that product-oriented and ideological campaigns, including social-issue messages and the “Gemoy” candidate branding, are more dominant than purely candidate-focused content. It also reveals that, despite a large follower base, engagement remains moderate and is driven more by Prabowo Subianto’s personal appeal than by institutional messaging.​